Food analysis : using ion chromatography - Muntean, Edward (De Gruyter STEM., 2022)
This book provides updated information about applications of ion chromatography (IC) in food science, such as food quality control, food authentication and analysis of residues in certain food products. Among liquid chromatography methods, IC can be considered one of the most valuable analytical tools, an advantageous environmentally friendly technique able to provide a convenient determination of various analytes such as anions, cations, organic acids, carbohydrates, amines, amino acids, aminoglycosides, proteins, peptides, etc. Recent developments such as in-line eluent generation systems, capillary IC and combustion IC, are also described. The book is intended to serve as an organized resource for students, researchers and food analysts, but can be a relevant support for researchers from related fields. It highlights that IC can be even more powerful and effi cient when more complex equipment is available, while proper knowledge empowers the user to obtain relevant data from this.